The sisters of Sinai : how two lady adventurers discovered the hidden Gospels - Soskice, Janet Martin (New York : Alfred A. Knopf, 2009)
In 1892, two sisters, identical twins from Scotland, made one of one of most important scriptural discoveries of modern times. Combing the library of St. Catherine's Monastery at Mount Sinai, they found a neglected palimpsest: one of the earliest known copies of the Gospels, a version in ancient Syriac, the language spoken by Jesus. This is the account of how two middle-aged ladies without university degrees uncovered and translated this text, bringing a treasure to world attention. This quintessentially Victorian adventure is partly a physical journey: when Westerners generally feared to tread in the region, the sisters Smith traversed the Middle East. It is also a journey of the mind: in an era when new discoveries in science and archaeology were rewriting the accepted understanding of the Bible's origins as well as those of humankind, a great contribution to knowledge was made by two whose only natural advantage was an astonishing gift for languages--From publisher description.
Cambridge, 13 April 1893 -- The birth and upbringing of the lady Bible-hunters -- The journey to the Nile -- The boat -- The perfect dragoman -- The search for the perfect mate -- Greece -- The estate of marriage -- The Cambridge antiquarian -- Heresy and mortality -- Sinai and von Tischendorf -- The perils of Bible-hunting -- The story von Tischendorf did not tell -- Setting out for Sinai -- The treasure in the dark closet -- The Cambridge party -- The disjoint expedition -- The final falling-out -- The devilish press and the Highland Regiment -- The Cambridge cold shoulder -- A lightning course in text scholarship -- In the company of orientalists -- Burying the hatchet -- Keepers of manuscripts -- Solomon Schechter and the Cairo Genizah -- In Cairo with Schechter -- Castlebrae -- The college's opening -- To the monasteries of the Nitrian Desert -- The active life -- The darkening to war -- Palimpsest.
"A Borzoi book"--T.p. verso.
"Originally published in Great Britain in slightly different form as Sisters of Sinai : how two lady adventurers found the hidden Gospels by Chatto & Windus ... London"--T.p. verso.
Includes bibliographical references (p. [301]-303) and index.
Keywords: Lewis, Agnes Smith, -- 1843-1926.; Gibson, Margaret Dunlop, -- 1843-1920.; New Testament scholars -- Great Britain -- Biography; Bible; Sinai, Mount (Egypt) -- Description and travel; Church history -- 20th century